A Comparative Study of Thinking Styles Among Sport-Practicing and Non-Practicing Students - Hamy, Ahmed Qasim Mohammed; KHalo, Khder Hasn (Journal of Educational and Psychological Sciences, 2022)
This research aimed to identify the common thinking styles among students who practice sports and those who don’t, and to detect the significance of the differences in that, according to some demographic variables. To achieve these objectives, the researchers used the descriptive method using a survey as well as a comparative method. The research sample consisted of (390) male and female students who were chosen in a deliberate way, in a pairing style, from the colleges of the University of Duhok for the academic year (2019-2020). The Arabic version of Harrison and Bramson scale was used. And the data was statistically processed using (mean, standard deviation, t-test for one sample and independent-samples, one-way analysis of variance (ANOVA), less significant difference (L.S.D) test, and Pearson Correlation Coefficient). The results of the study showed that the most common thinking style was the realistic thinking style, and the least common method was the synthetic method among students who practice sports and those who don’t. It was found that there is a statistically significant difference in the style of realistic thinking among students who practice sports and those who don’t. there is a statistically significant difference in the methods of thinking (synthetic, ideal, practical, and realistic) attributed to the variables of age. And there is a statistically significant difference in the method of practical thinking attributed to the academic specialization (scientific, literary) and in favor of the literary specialization. In light of the results, a set of recommendations and suggestions were presented.